POTENSI DAN KANDUNGAN LOGAM BERAT TEMBAGA (Cu) dan BESI (Fe) pada KERANG DARAH (Anadara granosa) di KABUPATEN NUNUKAN - Heppi Iromo (Jurnal Harpodon Borneo, 2010)
The purpose of this Research is to investigate heavy metal content in meet darah shell (Anadara granosa). Method to collecting of primary data is method survey with direct interview technique and analysed in laboratory. It were analysed heavy metal such as; Fe, and Cu, by used AAS. The result test laboratory for darah shell (Anadara granosa) with AAS is it can consumed because it have not contain dangerous heavy metal like  Cu but it detected contain little heavy metal Fe. Key Words:  Darah shell, Heavy metal Fe and Cu.